2020
DOI: 10.48550/arxiv.2008.00005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quenched fractions in the IllustrisTNG simulations: the roles of AGN feedback, environment, and pre-processing

Martina Donnari,
Annalisa Pillepich,
Gandhali D. Joshi
et al.

Abstract: We use the IllustrisTNG hydrodynamical simulations to show how the fractions of quenched galaxies vary across different environments and cosmic time, and to quantify the role AGN feedback and pre-processing play in quenching group and cluster satellites. At z = 0, we select galaxies with M stars = 10 9−12 M residing within ( R 200c ) massive groups and clusters of total host mass M 200c = 10 13−15.2 M in TNG100 and TNG300. The model predicts a quenched fraction of ∼70-90 per cent (on average) for centrals and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 93 publications
(156 reference statements)
2
20
0
Order By: Relevance
“…11 shows the number of TNG100 satellites belonging to each group as a function of orientation. It is evident from this figure that, for the specific galaxy and host mass ranges adopted in this work 49 , large-scale structure-sensitive satellites (red and orange symbols) are outnumbered by both star-forming, and particularly, satellites that quenched in their z ∼ 0 host halo, and thus, large-scale effects could only affect a minority of the satellite population.…”
Section: Ejective Agn Feedback At the Origin Of The Quenching Directi...mentioning
confidence: 85%
See 2 more Smart Citations
“…11 shows the number of TNG100 satellites belonging to each group as a function of orientation. It is evident from this figure that, for the specific galaxy and host mass ranges adopted in this work 49 , large-scale structure-sensitive satellites (red and orange symbols) are outnumbered by both star-forming, and particularly, satellites that quenched in their z ∼ 0 host halo, and thus, large-scale effects could only affect a minority of the satellite population.…”
Section: Ejective Agn Feedback At the Origin Of The Quenching Directi...mentioning
confidence: 85%
“…8 illustrates how the outcomes of the IllustrisTNG and Illustris cosmological numerical simulations compare. To marginalize over the possible differences in the overall quenching of galaxies between IllustrisTNG and Illustris 49 , also here we subtract the average quiescent fraction of both datasets. Extended Data Figure 6.…”
Section: Illustris Vs Illustristng Simulation Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that the group is in the early stage of assembly (Iodice et al 2017;Raj et al 2020) and it is located at the cluster infall distance where pre-processing is thought to occur (Lewis et al 2002;Gómez et al 2003;Verdugo et al 2008;Mahajan et al 2012;Haines et al 2015). The BGG is massive enough to experience efficient pre-processing (Donnari et al 2020) and Raj et al (2020) show that there are signatures of preprocessing in the group, with six of the nine late types having an up-bending (type III) break in their radial light profile. This indicates that the star formation may be halting in the outer disk of galaxies, although it is not yet clear what is driving the decline in star formation.…”
Section: The Fornax a Groupmentioning
confidence: 99%
“…Fujita 2004;Mahajan 2013;Roberts & Parker 2017;Cluver et al 2020). In particular, pre-processing is likely to be most efficient in massive (> 10 10.5 M ) galaxies residing in massive (10 13 -10 14 M ) groups (Donnari et al 2020). It has also been shown that pre-processing is responsible for the decrease in star formation activity for late type galaxies at distances between 1 and 3 cluster virial radii (e.g Lewis et al 2002;Gómez et al 2003;Verdugo et al 2008;Mahajan et al 2012;Haines et al 2015).…”
Section: Introductionmentioning
confidence: 99%